The Pro’s And Con’s Of Arbitration: A Study Of International Arbitration With Perspective Of Indonesian And Korean Law - Akhmad Al-Farouqi Sastrowiyono (Lex Renaissance, 2019)
Essentially, everyone wants their business torun well and smoothly, but dispute in the international business dealings can always happen, as internationalization generates new risks. Compared to disputes between domestic entities, international business dispute shave extra problem sincluding various jurisdictions, diverse legal systems and tradition, different procedures and oftenin volving more than one language. Arbitration is one of the way to settle the dispute but there are always pros and consaboutit. This will discuss about the advantages and disadvantages of arbitration from the point of view of both Indonesian and Korean Law, by using the normative-juridical method. In which the results conclude that there are important practical differences between litigation and arbitration from which the disputing parties can choose which settling way would they prefer according to the avantages and disadvantages.